Can and Should AI Help Us Quantify Philosophical Health? - de Miranda; Luis (Walter de Gruyter GmbH, 2025)
We explore the potential and limitations of using artificial intelligence to quantify philosophical health. Philosophical health is an approach to well-being defined as the dynamic coherence between thoughts, values, and actions in harmony with the world. As both AI and philosophical practice gain prominence in contemporary life, their intersection raises fundamental questions about measurement, meaning, and human flourishing. To substantiate our analysis, we present the Philosophical Health Compass (PHC), a quantitative instrument designed to assess six dimensions of philosophical wellbeing: bodily sense, sense of self, sense of belonging, sense of the possible, sense of purpose, and philosophical sense. Through analysis of this instrument, we investigate whether philosophical health – traditionally approached through qualitative exploration and dialogue – could meaningfully benefit from AI-assisted quantification. We introduce the C.I.P.H.E.R. Model (Crealectic Intelligence and Philosophical Health for Enriched Realities) as a human-in-the-loop framework for responsible integration of AI in philosophical practice. The article argues that while quantification offers valuable research opportunities, philosophical health assessment must preserve human sovereignty and philosophical pluralism. We conclude that AI can conditionally enhance philosophical health evaluation if implemented within boundaries that maintain the essentially human character of philosophical reflection, suggesting a complementary rather than substitutive relationship between quantitative tools and qualitative dialogue.